Introduction to gauge field theory - Bailin, David; Love, Alexander (New Delhi Overseas Pess (India), 2004)
Preface to first edition Preface to revised edition Path integrals - Problem, References Path integrals in non-relativistic quantum mechanics - Transition amplitudes as path integrals, The ground state to ground state amplitude, Ground state expectation values fro m, Problems, Refrences Classical field theory - Euler lagrange equations, Noether?"????s theorem, Scalar field theory, Spinor field theory, Massless vector field theory, Problems, References Quantum field theory of a scalar field - The Generating functional, The generating functional for free field theory, Green functions for free free field theory, The effective action and one particle irreducible, Green functions, Problems, References Scattering amplitudes - Scattering amplitude in quantum mechanics, Scattering amplitude in quantum field theory, References Quantum field theory with fermions - Path integrals over Grassman variables, The generating functional for spinor field theories, Propagator for the Dirac field Renormalisable theories of Dirac field, Renormalisable theories of Dirac fields and scalar fields, Feynman rules for yukawa interactions, Massless fermions, Scattering amplitudes with fermions, Problems, References Gauge field theories - Abelian gauge field theory, Non Abelian gauge field theories, Field equations for gauge field theories, References Feynman rules for quantum chromodynamics and quantum electrodynamics - Quantum chromodynamics, Problems in quantising gauge field theories, An analogy with ordinary integrals, Quantisation of gauge field theory, Feynman rules for gauge field theories, Scattering amplitudes with gauge fields, Problems, References Renormalisation of QCD and QED at one-loop order - Counter terms for gauge field theories, Calculation of renormalisation constants, The electron anomalous magnetic moment, Problems, References QCD and asymptotic freedom - The Renormalisation group equation, Deep inelastic electronic nucleon scattering, The wilson coefficients and moments
Keywords: Gauge fields (Physics); Particles (Nuclear physics)